It's time to move past biases against sex differences research: Commentary on Spets and Slotnick. Issue 3 (2nd October 2021) - Cahill, Larry
ABSTRACT: Neuroscience is uncovering sex influences at all levels of mammalian brain function at an accelerating rate. Unfortunately, persistent biases against the topic remain among some investigators. One is that sex influences are small and unreliable, despite the existence of no evidence supporting this general assertion. In this volume, Spets and Slotnick provide clear evidence for a consistent sex influence on one aspect of human cognition, retrieval from long-term memory.